Urban criminology: thinking beyond the paradox - Atkinson, Rowland (Criminological encounters, 2020)
Criminology has often taken the city as the de facto space of its intellectual project. Despite this, criminology has never been urban. Criminology has implicitly focused on problems of the city while rarely being for the city, in many cases contributing to the case against urban living. "Mainstream" formulations of the criminological project, in the forms of administrative and positivist approaches, have not been a friend to the city ‒ especially to its more excluded, its deprived, and to communities experiencing enduring forms of discrimination. Indeed, many such urban communities have often been identified as forming the spatial and social constitution of the urban crime problem. Such a city-facing, yet anti-urban, criminology has been realised in rhetorical and discursive terms, but also in its state and policy formulations. Its most significant examples being defensible space, zero tolerance policing, and situational crime prevention. In this sense, the idea of an urban criminology has seemed paradoxical. We reflect here on a more critical and progressive engagement with crime in cities, suggesting the need for a robust and closer dialogue between critical urban studies and critical criminology.